Digital Literacy Research in Education : Trends and Insights - Febi Adriana Mutiara Sogalrey; Febriani Safitri; Meylani Aljeinie Tijow; Desy Anita Karolina Sembiring; Putri Ellen Gracia Risamasu (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This study explores the latest trends and insights on digital literacy in education through bibliometric analysis. Using data from the Scopus database and VOSviewer software, the study analyzed 3,386 publications on digital literacy in educational contexts from 2015 to 2024. Qualitative content analysis methods were used to code and interpret text data. Findings show a significant growth in the number of publications, with the highest peak in 2023. The United States led the research contributions, followed by Spain, the United Kingdom, and Indonesia. The dominant field of study was social sciences, followed by computer science and engineering. Lead authors include Makhachashvili, R., with affiliations at Universidad Salamanca and Monash University. Significant trends identified include an increased focus on digital health, information accuracy, and online learning in response to the COVID-19 pandemic. The study emphasized the importance of digital literacy as a critical skill in a digital society, and identified gaps in the existing literature. This encourages further research to explore the impact of digital literacy on student learning outcomes and education policy. These findings can be a guide for developing a more relevant curriculum by integrating local cultural and technological elements, as well as improving the quality of education.